PENGARUH RELAKSASI YOGA TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III MENGHADAPI PERSALINAN DI KLINIK RUMAH PUSPA BEKASI TAHUN 2017 - Tantri Sitanggang; Afnita Lutfiani (STIKes IMC Bintaro, 2017)
Anxiety in pregnant women is common happen in primigravida or at the age of pregnancy at third trimester especially before the delivery process. One way to overcome this care is yoga relaxation. Research aimed to determine the influence of relaxation yoga to anxiety levels on pregnant women at third trimester dealing with labor in Clinic Rumah Puspa Bekasi in 2017. This research design of Quasy Experimental with the sample were as 30 respondents divided into two groups as 15 respondents were the experiment group and as 15 respondents were the control group. Technique of the sample used was Purposive Non Random Sampling. Data collection used a measuring instrument anxiety that was the questionaire (HARS). Data were analyzed by a test paired sample t-test and an independent t-test. The results of the analysis univariat shows that the anxiety group experiment lower than the control group with 86,7% didn’t experienced anxiety and 13% were mild anxiety in the experiments group while the rest of 13% were mild anxiety, 60% were moderate anxiety and 26,7% heavy anxiety on the control group. The results of the analysis bivariat test paired sample t-test, group experiment α<0,05. In the independent t-test, pretest in both groups α>0,05 and posttest in both groups α>0,05. In conclusion is the yoga relaxation is needed to decrease the anxiety levels of pregnant women at third trimester. It is expected that pregnant women at third trimester more digging knowledge on how to deal with the anxious ahead of childbirth or during pregnancy as practice yoga relaxation in pregnancy.